IMPLEMENTASI SAW (SIMPLE ADDITIVE WEIGHTING) UNTUK REKOMENDASI PRODUK TOKO - Adi Nugroho, Baskoro; Andreas Sutanto, Felix (Information Technology and Telematics, 2018)
ABSTRACT Koningsize Shop is a store that sells various clothes and shoes in surabaya city. But since the stands buyers must come to the store to make a purchase. Data collection methods used by the author is the method of observation, interview and literature study. Methodology of system development in this research using Waterfall. The result of this research is the creation of a system used to recommend the product to the buyer when it is logged into Koningsize Store web, and in the making of this research using SAW (Simple Additive Weighting) method which is aimed to facilitate the management of product recommendation at Koningsize Shop. Keywords: Product Recommendations, SAW, Waterfall, PHP